2016
DOI: 10.1093/workar/waw034
|View full text |Cite
|
Sign up to set email alerts
|

Activities Matter: Personality and Resource Determinants of Activities and their Effect on Mental and Physical Well-being and Retirement Expectations

Abstract: Remaining active throughout the lifespan is central to healthy aging. The current study tests a model derived from investment and resource theories that examines the extent to which activities mediate the relationship between individual differences in personality and resources on mental and physical well-being and retirement expectations. A subsample (N = 400; 58% female) of participants from the nationally representative Health and Retirement Study (HRS) was used.Self-reported activities were grouped into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Theoretical and empirical reviews (e.g., Wang & Shultz, 2010;Zhan et al, 2009a) showed that educational level has a negative relationship with retirement decisions. Beier et al (2016) also viewed education as a cognitive resource and found that those with higher educational attainment are more likely to continue to work after age 65. Based on these findings, we argue that education can not only predict older workers' retirement decisions, but also moderate the relationship between HIWPs and retirement decisions.…”
Section: Moderating Effects Of Individual Characteristicsmentioning
confidence: 99%
“…Theoretical and empirical reviews (e.g., Wang & Shultz, 2010;Zhan et al, 2009a) showed that educational level has a negative relationship with retirement decisions. Beier et al (2016) also viewed education as a cognitive resource and found that those with higher educational attainment are more likely to continue to work after age 65. Based on these findings, we argue that education can not only predict older workers' retirement decisions, but also moderate the relationship between HIWPs and retirement decisions.…”
Section: Moderating Effects Of Individual Characteristicsmentioning
confidence: 99%
“…Social groups are especially beneficial post-retirement when they involve shared group activities (Haslam et al, 2019). Consistent with the link found between social group memberships and positive anticipation and experience of identity change in retirement, having a variety of activities positively shapes general retirement expectations and contributes to healthy post-retirement aging (Beier et al, 2018), while sharing these activities with a partner can increase relationship satisfaction (Bozoglan, 2015). Interventions pre-and post-retirement that aim to preserve work-based group affiliations (e.g., alumni) and increase the number of social groups and subsequent activities in which people participate (e.g., volunteer pathways, retiree community groups) might provide opportunities for older adults to continue to make positive contributions towards their community and identity after exiting the workforce.…”
Section: Implications For Practicementioning
confidence: 71%
“…We do not present the measurement matrices here for the purpose of brevity. Interested reader can refer to Arthur and Day (1994) We coded physical health by summing the number of health conditions, which is a standard approach to code physical health in empirical studies based on the HRS (e.g., Beier et al, 2018;Barnes-Farrell & Petery, 2018;Wang, 2007) or the SHARE (e.g., Madero-Cabib et al, 2020;Shai, 2018;Siegrist et al, 2007) data sets.…”
Section: Appendix a A Summary Of The Five Empirical Studies Examining...mentioning
confidence: 99%